Avoiding Unnecessary Surgery in Acute Longus Colli Calcific Tendinitis: A Clinical Image of a Retropharyngeal Abscess Mimicker - Brandon M Nielsen; Oluyemi O Omotoso (HCA Healthcare Journal of Medicine, 2026)
Acute calcific tendinitis of the longus colli (LCT) is a rare, benign condition that frequently mimics retropharyngeal abscesses (RPA), a true surgical emergency. We present a 34-year-old woman presenting with 4 days of severe posterior neck pain, stiffness, and odynophagia. Initial evaluation revealed significantly elevated inflammatory markers (erythrocyte sedimentation rate [ESR] 113 mm/hr, C-reactive protein [CRP] 128 mg/L) and leukocytosis, raising immediate concern for deep neck infection. Contrast-enhanced computed tomography (CT) demonstrated a retropharyngeal fluid collection; however, the absence of peripheral ring enhancement and the presence of a pathognomonic calcification anterior to the C1 arch pointed toward LCT. This distinction allowed for successful conservative management with NSAIDs and steroids, preventing unnecessary surgical drainage. This case underscores the critical utility of contrast CT in distinguishing the benign, non-enhancing effusion of LCT from the ring-enhancing abscess of RPA. Recognition of this radiographic pattern is essential to avoid potential morbidity associated with misdiagnosis and overtreatment.